SOLUBILITY DIAGRAM OF THE SYSTEM NaClO3•CO(NH2)2 - NH4H2PO4•NH2C2H4OH - H2O (Scientific journal of the Fergana State University, 2026)
In this work, the solubility of components in the ternary system NaClO3∙CO(NH2)2 - NH4H2PO4·NH2C2H4OH - H2O was investigated, and the temperatures of complete crystallization were determined in the range from -46.0 °C to +70.0 °C. Based on the collected data, a polythermal diagram was constructed reflecting the boundaries of the crystallization regions of such substances as sodium monocarbamidochlorate, monoethanolamine - ammonium phosphate and ice. It was found that the system is characterized by a simple type.